Suicide on Railroad Rights‐of‐Way: A Psychological Autopsy Study. Issue 6 (20th June 2014) - Berman, Alan L.; Sundararaman, Ramya; Price, Andrea; Au, Josephine S.
<x xml:space="preserve">Abstract</x> Findings from 55 psychological autopsies of decedents who perished on U.S. railroad rights‐of‐way between October 1, 2007, and September 30, 2010 are reported. Described are distal, proximal, and contextual factors of risk; understandings of why these suicides occurred on railroad rights‐of‐way; and opportunities for prevention of similar suicides. International comparisons of suicides on railroad rights‐of‐way are made to highlight distinct findings regarding U.S. cases. Decedents studied exhibited considerable predisposing risk for suicide, with a high prevalence of severe mental disorders and substance abuse. In addition, a number of acute risk factors were commonly observed, notably suicide ideation, hopelessness, anxiety, and anger. In the context of that acute risk, associated situational variables and a relative absence of protective factors are described.